2011
DOI: 10.3912/ojin.vol16no02ppt01
|View full text |Cite
|
Sign up to set email alerts
|

Nursing at its Best: Competent and Caring

Abstract: An award-winning journalist spoke to a group of students during their first month in a baccalaureate nursing program, challenging the nursing profession to abandon its image of nurses as angels and promote an image of nurses as competent professionals who are both knowledgeable and caring. This presentation elicited an unanticipated level of emotion, primarily anger, on the part of the students. This unexpected reaction prompted faculty to explore the students’ motivations for entering the nursing profession a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Constant bedside NMW care may be a more important intervention than first thought (Mokhtari et al., 2022). The relative importance of the NMW, to deliver person‐centred comprehensive healthcare to infectious patients, needs further elevation to more actively and accurately measure that impact (Rhodes et al., 2011; Ullman & Davidson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Constant bedside NMW care may be a more important intervention than first thought (Mokhtari et al., 2022). The relative importance of the NMW, to deliver person‐centred comprehensive healthcare to infectious patients, needs further elevation to more actively and accurately measure that impact (Rhodes et al., 2011; Ullman & Davidson, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to problems belongs to a new issue (Hawari, 2006). Rhodes stated that the intellectual level of a student relates to the challenge to his intellect in order for them to gain the knowledge, abilities and skills involved in nursing (Rhodes, M. K., Lazenby, R., & Moris, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…They will also have the right to CB (Murphy, F. & Robert, 2009). Rhodes identified that the intellectual level of a student will challenge his intellect as a part of gaining their nursing knowledge and skills (Rhodes, M. K., Lazenby, R., & Moris, 2011).…”
Section: Introductionmentioning
confidence: 99%